2023
DOI: 10.5173/ceju.2023.252
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics vs radiologist in bladder and renal cancer. Results from a systematic review

Abstract: Introduction Radiomics in uro-oncology is a rapidly evolving science proving to be a novel approach for optimizing the analysis of massive data from medical images to provide auxiliary guidance in clinical issues. This scoping review aimed to identify key aspects wherein radiomics can potentially improve the accuracy of diagnosis, staging, and grading of renal and bladder cancer. Material and methods A literature search was performed in June 2022 using PubMed, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The field of robotic urology is on the edge of a transformative era, thanks to the synergistic integration of advanced robotics [45], artificial intelligence (AI) [46], and cuttingedge pre-and intraoperative imaging technologies [47,48]. AI algorithms are able to analyze patient data, medical history, and imaging to predict the potential for intra-and postoperative complications [49].…”
Section: Discussionmentioning
confidence: 99%
“…The field of robotic urology is on the edge of a transformative era, thanks to the synergistic integration of advanced robotics [45], artificial intelligence (AI) [46], and cuttingedge pre-and intraoperative imaging technologies [47,48]. AI algorithms are able to analyze patient data, medical history, and imaging to predict the potential for intra-and postoperative complications [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, radiomic features have been integrated into the BCa diagnosis workflow by offering preoperative staging and tumoral grading predictions based on bladder mpMRI acquisitions. It has been shown that the addition of textural features increased the specificity of BCa diagnosis by 12% and reduced the lymph nodes understaging rate by 36% when compared to the radiologist’s mpMRI interpretation alone [ 9 ].…”
Section: Introductionmentioning
confidence: 99%